The Effectiveness Test Atung Methanol Extract (Parinarium Glaberimum Hassk) as a Fly Repellent for Salted Skipjack Tuna - Debby D. Moniharapon; Trijunianto Moniharapon; F. Pattipeilohy; M. N Mailoa (International Journal of Educational Research Excellence (IJERE), 2023)
House flies (Musca domestica) and green flies (Calliphora vomitoria) are members of the Muscidae family which are commonly found in residential areas in Indonesia. The habit of houseflies and greenflies in searching for food in wet household waste has the potential to make them vectors of pathogens that cause dysentery , cholera, typhoid, diarrhea and worms . Atung ( Parinarium glaberimum Hassk) contains secondary metabolites, namely: alkaloids, flavonoids, terpenoids, phenol, saponins and tannins. The phytochemical compounds in Atung have the potential to act as a fly repellent (Repellent). The aim of this research was to determine the landing power of fly repellent on Atung methanol extract. This research was designed using a simple RAL experimental method with 4 treatments and 3 repetitions. Concentration variations 0% (control), 1%, 2%, from 4%. Data analysis used the Anova statistical test analysis version SPSS 24 at a significance level of 0.05. The results of the research showed that the higher the concentration of Atung methanol extract used in the fly repellent, the less the fly's ability to land on salted skipjack tuna. The protective ability of the repellent against house flies and green flies is 83% for a methanol extract concentration of 1%, 88% for a methanol extract concentration of 2%, and 100% for a methanol extract concentration of 4%. Atung methanol extract has the potential to be used as an active ingredient. Effective repellent against houseflies and greenflies.